Effects of an Isolated Complete Right Bundle Branch Block on Mechanical Ventricular Function. (21st October 2015) - Zhang, Qin; Xue, Minghua; Li, Zhan; Wang, Haiyan; Zhu, Lei; Liu, Xinling; Meng, Haiyan; Hou, Yinglong
Abstract : Objectives: The purpose of this study was to investigate the effects of an isolated complete right bundle branch block on mechanical ventricular function. Methods: Two groups of participants were enrolled in this study: a block group, consisting of 98 patients with isolated complete right bundle branch blocks without structural heart disease, and a control group, consisting of 92 healthy adults. The diameter, end‐diastolic area, end‐systolic area, and right ventricular (RV) fractional area change were obtained to evaluate morphologic and systolic function by 2‐dimensional sonographic technology. Systolic and diastolic velocities and time interval parameters were measured to assess mechanical ventricular performance using pulsed wave tissue Doppler imaging. Results: Although there was no significant difference in the RV fractional area change between the patients with blocks and controls, the diameter, end‐diastolic area, and end‐systolic area of the RV were significantly larger in the patients with blocks ( P < .05). In the patients with blocks, the peak velocities during systole and early diastole and the ratio of the peak velocities during early and late diastole decreased. The block group had a prolonged pre‐ejection period, electromechanical delay time, and isovolumic relaxation time, a decreased ejection time, and an increased pre‐ejection period/ejection time ratio, and the myocardial performance index (Tei index) at the basal RV lateral wall was significantly increased. There were no significant differences in any echocardiographic parameters at different sites of the left ventricle. Conclusions: In patients with isolated complete right bundle branch blocks, systolic and diastolic functions are impaired in the RV, and follow‐up is needed.